MANAJEMEN PENDISTRIBUSIAN ZAKAT PADA BADAN AMIL ZAKAT NASIONAL DI KABUPATEN ENREKANG - Mutmainna Mutmainna; Muhammadiyah Muhammadiyah; Haerana Haerana (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
This study purposed to find out how the Distribution Management in Baznas of Enrekang Regency became the best distribution management in South Sulawesi. This study used descriptive qualitative methods, it provided an overview of the Management of Zakat Distribution at the National Zakat Agency in Enrekang Regency where the researcher interviewed 4 informants. Data sources consisted of primary data obtained through interviews while secondary data was obtained from official documents, records, reports and files that could be supported by complete primary data. According to The National Amil Zakat Agency; Badan Amil Zakat Nasional (BAZNAS) of Enrekang Regency stated there were criterias in distribution management namely: Planning, Organizing, Mobilizing and Supervising. Based on the results of this study showed that the management of the zakat distribution in the National Enrekang Regency was running very well because the National Enrekang Regency did distribution according to the existing regulations in the central Baznas and according to religious provisions.Keywords: Distribution, Management, ZakatABSTRAKPenelitian ini bertujuan untuk mengetahui, bagaimana Manajemen Pendistribusian di Baznas Kabupaten Enrekang Sehingga menjadi yang terbaik manajemen Pendistribisiannya di Sulawesi selatan. Jenis penelitian ini menggunakan metode deskriptif kualitatif, yaitu peneliti bermaksut untuk memberikan gambaran mengenai Manajemen Pendistribusian Zakat Pada Badan Amil Zakat Nasional di Kabupaten Enrekang dimana penulis mewawancarai 4 orang . sumber data terdiri dari data primer yang di peroleh melalui wawancara sedangkan data sekunder di peroleh dari dokumen-dokumen, catatan-catatan, laporan maupun arsif resmi yang dapat didukung dengan kelengkapan data primer. Hasil penelitian yang dilakukan di Badan Amil Zakat Nasional (BAZNAS) Kabupaten Enrekang. Dalam manajemen pendistribusian terdapat kriteria yaitu : Perencanaan, Pengorganisasian, Penggerakan, dan Pengawasan. Berdasarkan Hasil Penelitian tersebut menunjukan bahwa Manajemen Pendistribusian zakat di baznas Kabupaten Enrekang berjalan dengan sangat baik karna baznas Kabupaten Enrekang Melakukan Pendistribusian Sesuai aturan-aturan yang ada di Baznas pusat dan sesuai ketentuan agama. Kata Kunci : Manajemen Pendistribusian